How Do Coaches Identify With Their Role as a Coach? Exploring Coach Identity Through a Role Identity Theory Lens - Pope, J. Paige; Hall, Craig R.; Tobin, Danielle (Identity (Mahwah, N.J.), 2014)
This study was designed to explore the coach identity through the meanings and prominence ascribed to the coaching role from a role identity theory perspective (McCall & Simmons, 1978 ). Participants (n = 8), ranging in age from 22 to 61 years old, reported coaching on average about 19 years and primarily coached university- to national-level athletes. Results from the semistructured interview with the participants yielded a thematic tree that consisted of two higher-order themes (coach meanings and coach identity prominence). Coach meaning was refined into three categories: coaching behavioral expectations, coaching characteristics, and ultimate coaching purposes. Coach identity prominence was composed of two categories: coaching centrality/importance and coaching emotions. There were 21 lower-order themes that were associated with these categories. Results from this study provided initial support for the conceptualizations put forth by role identity theorists, and offered initial insight for (a) the development of identity-based coaching scales, and (b) examination of the coach identity nomological network.